ACCOUNTING ERRORS AND FRAUDS AND THE FORENSIC ACCOUNTING PROFESSION IN DETECTING FRAUD - Demir, Cumhur; Yıldız, Abdunnur (Bilgi Yolu Eğitim Kültür ve Sosyal Araştırmalar Merkezi: BİLSAM, 2022)
Developments in the economic and technological fields in the world have caused changes in the structure and policies of the enterprises and facilitated the businesses to operate on a global scale by increasing their business volumes. This development and change have brought some positive effects for businesses as well as some negative effects. One of these primary negative effects is that the erroneous and fraudulent transactions observed in the accounting records of some businesses are performed much more professionally. Forensic accounting has beenapplied profoundly in the world, especially for the last 40 years. It is a profession that covers many disciplines such as accounting, law, audit, statistics, psychology and information technologies, deals with the solution of legal problems that have been submitted to courts, and deals with the detection, prevention and solution of crimes such as fraud and irregularity. Although forensic accounting profession has a long past in many countries, it is a new business area in Turkey.

Dünyada ekonomik ve teknolojik alanlarda meydana gelen gelişmeler, işletmelerin yapılarında ve politikalarında da değişikliklere yol açıp, işletmelerin iş hacimlerini büyüterek küresel boyutlarda faaliyet göstermelerini kolaylaştırmıştır. Bu gelişim ve değişim, işletmeler için birtakım olumlu etkilerde bulunduğu gibi bazı olumsuz etkileri de beraberinde getirmiştir. Bu olumsuz etkilerin başında bazı işletmelerin muhasebe kayıtlarında gözlemlenen hatalı ve hileli işlemlerin çok daha profesyonelce yapılıyor olması gelmektedir. Adli muhasebe, dünyada özellikle son 40 yıldır ciddi bir şekilde uygulanmaktadır. Adli muhasebe, hukuk, denetim, istatistik, psikoloji ve bilgi teknolojileri gibi birçok disiplini içine alan, mahkemelere intikal etmiş olan hukuki sorunların çözümüyle ilgilenen, hile ve usulsüzlük gibi suçların tespit edilmesi, önlenmesi ve çözümüyle uğraşan bir meslek dalıdır. Adli muhasebecilik mesleği, dünyanın birçok ülkesinde daha eski bir geçmişe sahip olmasına rağmen, Türkiye’de daha yeni sayılabilecek bir durumdadır.
MUHASEBE HATA VE HİLELERİ VE HİLELERİN ORTAYA ÇIKARILMASINDA ADLİ MUHASEBECİLİK MESLEĞİ